Does the plankton community follow the horizontal water quality heterogeneity in a tropical urban reservoir (Guarapiranga reservoir, Sao Paulo, Brazil)? - Nishimura, Paula Yuri; Meirinhol, Patricia do Amaral; Moschini-Carlos, Viviane [UNESP]; Martins Pompeo, Marcelo Luiz (Asoc Espan Limnol-mislata, 2014)
Reservoirs exhibit a marked degree of spatial heterogeneity, and environmental heterogeneity directly affects organism distribution and community composition. The objective of this study was to investigate the spatial horizontal heterogeneity of the planktonic communities along the longitudinal axis of the Guarapiranga reservoir (Sao Paulo, Brazil). We sampled nine stations along the Guarapiranga reservoir longitudinal axis for physical, chemical and biological variables. In addition, we analysed phytoplankton and zooplankton communities. To explore the data, we applied multivariate techniques, such as cluster hierarchical analysis and discriminant analysis. Our results showed a clear tendency towards compartmentalisation of the epilimnetic layers in this reservoir, especially when based on water quality. Three main compartments were observed: 1) the Embu-Gracu region, the upper part of the reservoir, more protected and less eutrophic; 2) the Parelheiros region, a very eutrophic branch of the reservoir; and 3) the lower part of the reservoir, with eutrophic and lacustrine characteristics. The groups formed by the cluster analysis based on the plankton data did not coincide with the groups based on water quality. These different outcomes indicate that the water quality, phytoplankton and zooplankton communities captured different features from the epilimnetic layer in the longitudinal axis of the Guarapiranga reservoir. Importantly, the phytoplankton and zooplankton communities in the dam region were altered, directly or indirectly, by copper sulphate treatment. Therefore, phytoplankton biomass is being driven by forces other than the forces intrinsic to the reservoir, such as human-induced losses. Consequently, zooplankton structure is being affected as well.

Los embalses muestran un marcado grado de heterogeneidad espacial y la heterogeneidad ambiental afecta directamente a la distribución de los organismos y la composición de la comunidad. El objetivo de este estudio fue investigar la heterogeneidad espacial horizontal de las comunidades planctónicas a lo largo del eje longitudinal de Embalse Guarapiranga (Sao Paulo, Brasil). Se tomaron muestras en nueve estaciones a lo largo del eje longitudinal de Guarapiranga (datos físicos, químicos y biológicos). Además, se analizaron las comunidades de fitoplancton y zooplancton. Para explorar los datos, se aplicaron técnicas multivariantes, como el análisis de conglomerados jerárquico y análisis discriminante. Los resultados muestran una clara tendencia a la compartimentación de las capas epilimnéticas en este embalse, especialmente basada en la calidad del agua. Se evidenciaron tres compartimentos principales: 1) la región de Embu-Guaçu, cabecera del embalse, más protegida y menos eutrófica, 2) la región de Parelheiros, un tramo de río muy eutrófico y 3) la parte del embalse, cerca de la presa, con características eutróficas. Los grupos formados por el análisis de conglomerados jerárquico basado en los datos del plancton no coinciden exactamente con los grupos basados en la calidad del agua. Estos resultados indican que la calidad del agua y la comunidad del fitoplancton y zooplancton están influenciadas por diferentes características de la capa epilimnética en el eje longitudinal del Embalse Guarapiranga. Es importante destacar que el fitoplancton y zooplancton en el embalse fueron alterados, directa o indirectamente, por un tratamiento con sulfato de cobre. Por lo tanto, la biomasa del fitoplancton está condicionada por acciones humanas, distintas a las inherentes al embalse. En consecuencia, la estructura del zooplancton también está siendo afectada.
Keywords: Phytoplankton; Zooplankton; CSR-strategists; Compartmentalisation; Fitoplancton; Zooplancton; Estrategias CRS; Compartimentación